Os Índios Potiguara: memória, asilo e poder - Simões, José Manuel (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations PhD in Global Studies (D-GLS); University of Saint Joseph

The current situation of Macau secondary multi-media teaching in physics - Ao, Wai Chi (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Curriculum development of MICE in tertiary education in Macao - Chan, Kam Lun (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Fashion education and the fashion industry in Macau linked through an NGO - Chan, Victoria Alexa Kuan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Moral values in education: a case study of one secondary school in Macau - Chen, Xin Wang (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An interpretative study of three aspects of teacher retention, turnover, and attrition in Macau - Cheong, Ngai Hong (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Changing minds: an analysis of the impact of the discovery learning methodologies on the student's attitude towards learning - Churchill, Geoffrey Raymond Alan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Educational technology and the learning of history in a middle school in Macao - Lai, Su Kei (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Inclusive education in Macau: a dual teacher-parent perspective - Lam, Sao Lan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Motivation and factors affecting Japanese learning at the institute for tourism studies - Lao, Meng (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A school-based investigation of school disipline in Macau - Lei, Chi Hang (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Developing a community-based science curriculum for primary school students in Macau - Ng, Shuk Yan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Percepções de justiça na avaliação de alunos: exploração de situações no ensino secundário em Macau - Pablo, Alberto Manuel da Conceição (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

As tic na aprendizagem da língua Portuguesa - Simões, Joana Rodrigues (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A study of the factors affecting th retention of secondary English teachers in Macao private schools - Tai, Lai Kan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Teachers' perceptions of professional development: a case study of two schools in Macau - Wong, Fong Lei (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The impacts of cultural diversity on organization in Macau - Chan, In Choi (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of GAP Inc - Cheong, Im Seong (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The generics pharmaceutical industry: the present and future of antibiotics - Ng, Kin Wa (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Vcall - Wong, Io Leong (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

MB intelligence-consultancy limited - Andorinho, Rita da Costa (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Marketing strategies for a global textbook company to expand into the secondary school market in Macau - Chan, Ka Pou (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Implementation of a centralized ERP system for the supply chain department in Melco Crown Entertainment - Fong, Tou Vai (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management issues in Hong Kong - Iun, Mio Hong (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management in Macao: global, regional, local forces and critical challenges - Lampo, Alessandro (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Improving customer loyalty programs to increase market share - Lei, Sut Na (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Profile technician business plan 2011-12 - Silva, Miguel P. F. Gomes da (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management style changes in: Malaysia - Tam, Mei San (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Study on the managerial style change in Australia - Tang, Pou I. (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Developing an employer brand for the judiciary police: a consultants' report - Chan, Hao Man (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study of management transition in South Korea - Chan, Wai Ip (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study of management change in Egypt - Chan, Wai Kei (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

"Balm Balm" the U.K's leading 100% organic skincare company-market opportunity in Macao - Chan, Weng Ian (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study of management transition in the United States - Choi, Hoi Lam (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Cosultant's report for improving on-time delivery performance and inventory control of commercial business unit (CBU) in semiconductor industry - Chong, Lai Ha (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Developing a customer call-center in Macau for a beverage company - Gunawan, Albert (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Explanatory study of management style changes in the Philippines - Lam, Sok Chan (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Distribution of Meiji baby milk powder in Macao - Leong, Chi Cheong (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Employee climate survey of Zhuhai Zhongfu Enterprise Ltd. Co - Liu, Yan Mei (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of FedEx corporation - Olalekan, Adebiyi (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Tencent - Sou, Fai Wong (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of the Coca Cola Company - Chan, Weng Chun (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A new talent management strategy for the Macau labour bureau-labour inspection department - Conceição, Beatriz Seabra Da (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of Dell, Inc - Fong, Pui Wa (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of Nu Skin Enterprises, Inc - Kuok, Man Lei (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A valuation of Thomson Reuters - Leong, Kam Wa (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A study of German management and its management style changes - Ng, Chi Lan (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A strategic report to help increase the company's growth in the it industry - Ng, Fong Chi (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A strategic business development report for jewellery retail industry - Sam, Wai Heng (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study of the training and development needs in the Macau hotel industry - Tou, Cheng I. (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Analysis of employee turnover intention within Macau gaming industry: a case study of Starworld casino - Tou, Weng I. (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of the Hewlett-Packard company - Un, Cheng Leong (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of target corporation - Vong, Karen (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A training plan develop reort for call center industry - Vong, Keng Chi (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valucation study of Target Corporation - Vong, Kuan Vai (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Raising the quality of secondary education in Macao with effecive government funding in private schools: a case study in Santa Rosa de Lima (a private high school) - Man, Kam Tou (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Striving for sucess in governmental management: a work report on administration and government policy of the monetary authority of macao - Choi, Lai Si (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Social unrest in Xinjiang in the 21st century: crisis of the Chinese multinational state? - Flores, Rui (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The BRICS and the global order in the early XXI century - Kern, Rafaela Chemale (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Work Report: the Venetian Macao resort hotel - Lei, Iok Kei (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Dealing with a changing society: a work report on further development of the government infnormation bureau - Loi, I. Man (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Strategic management coping with contemporary globalization: a work report on the administrative policy of the mpi - bell centre of english - Ma, Si Ka (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Striving for success in diversities: a case study on perspective of administrative and government policy of the cultural affairs bureau - Wong, Sut Ieng (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Achievement goals, academic motivation and academic emotions - Sun, Sok U. Rosa Maria (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Academic self-concept and non academic self concept on test anxiety the mediating role of academic emotion - Wong, Nga Na (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The influence of socialiration tactics and causality orientations on eross-evltuaal adjustment - Bilugan, Marifi Lagan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Crisis in motivation: exploring the factor structure of academic amotivation among school student in Macau - Chao, Josefina (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

General affective dispositions on academic emotions: exploring the general and specific dimensions of emontions as determinants of students' emotional experiences - Oberhauser, Petra (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A proposed young persons community center for prevention and intervention program for vulnerable young persons - Olivena, Qlinto (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The efficacy of an empathy training program for young offenders in the Macao youth correctional - Wong, Pak Kei (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The outcome of mind over old-age depression program on order people with depression in one Macao elderly day center - Yang, Liu (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The influence of social companions on affect and life satisfaction - Chao, Hang In (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Academic emotions as mediators between achievement goals and academic: achievement - Kot, Sok Kuan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The efficacy of self-control training in the Macao youth correctional institute: changes in the impulsiveness and emotion stability of young offenders - Lei, Joana (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Gender differences in self-reported depression: an examination of gender bias, social desirability and stereotype threat - Ng, Lai Va (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Exploring the therapeutic value of dancing among the selected Chinese women in Macau - Rosario, Elzira Jonas Do (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The influence of parental expectations on the psychological distress of Chinese college students in Macao - Sam, David (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Public and family stigma of seeking psychological help among Chinese college students - Sou, Kuai Long (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Academic self-concept and non-academic self-concept on test anxiety: the mediating role of academic emotions - Tam, Chi Kuan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Fernand Braudel and China - Lau, Nga Lai (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Comparision of modern cultural tourism in Hong Kong and Macao - Mui, Ho Yan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Nineteenth-Century Women's Travel Writings: A Case Study on Ana D'Almeida's Dairy and Chinese Women's Writing - Leong, Si Kei (University of Saint Joseph, 2011)
We live in an era in which critique of the West has become a deep-rooted phenomenon of the lives of non-Europeans. This paper contributes to the study of European women perception of South East Asia as mirrored in travel writing accounts and, independently but syncronic, of the Chinese women poets who wrote during a period a few decades before and after the mid nineteenth century. I shall be analysing the Western concept of femininity and domesticity in relation to and symultaneously attempting to reformulate Edward Said’s concept of Orientalism. Central to my research method is the fact that I am trying to add to to a traditional Western-oriented gender issues approach - baded on a review of the mid- nineteenth women travel writers - a reversed view, that being the representation of the Orient emerging from the vision of Chinese women literature. My research not only focuses on the literariness of travel writing, which has been widely neglected, but also on a vision of the Orient that is represented by some Chinese women writers in the nineteenth century –Gan Lirou 甘立媃 (1743-1819) and Lü Bicheng 呂碧城 (1883 – 1943). My research is not a survey study of Chinese literature, and it does not claim to be exhaustive. Instead, I attempt to systematize the problem of Western representations of the Orient by taking Ana d’Almeida’s diary, A Lady’s Visit to Manilla and Japan, as central reference and source of conceptual classification. From there, I am trying to further some gender issues drawn from Ana d'Almeida's text and identify symetric instances of those representations, if present, in Chinese literary texts written roughly in the same historical period. Expending Edward Said’s Orientalism, this paper tries to challenge the classic univocal Orient-Occident approach and to mirror Western Orientalist and pseudo- Orientalist ideas into contemporary Chinese writings. This is also meant to be an introduction to this cross-cultural comparative approach of feminity and domesticity open for further contributions in gender studies as well as in fields bordering social history, history of literature, literary theory and cultural anthropology
Keywords: Thesis and Dissertations PhD in History (D-HIS); University of Saint Joseph Thesis and Dissertations PhD in

Accounting in Macau: A Historical Perspective from 1970s until 2008 - Lam, Ching Chi (University of Saint Joseph, 2011)
The current research study embraced the objectives to investigate the transformation of accounting in Macau from the first set of accounting legislations in 1970s, through the first set of accounting standards in 1983, until a year after the first application of international accounting standards, by 2008. From the transformation, the role taken by accounting in the economy and the factors that have influenced the transformation were intended to identify. Through the historical picture, findings have supported and expanded the theoretical concepts that accounting was taking both active and passive roles in the economy. Furthermore, they also supported the theoretical concepts that culture, economic environment, political environment and education influenced the transformation of accounting. The objectives have been structured through three research issues identified from the analysis of past literatures. Five qualitative and quantitative research studies have been carried out, using primary and secondary data from both primary and secondary sources. In-depth interviews on 13 representative respondents of the government, the profession, the industry and the academia, directly or in-directly related with accounting have been done. A case study on a company doing business in Macau since 1970s was included to enrich, supplement and evaluate the findings on the accounting practice of Macau. Based on the findings, a model has been constructed that represented the interaction between accounting and the different factors of the economy. Contributions from the research findings have enriched the research literatures on the area of accounting history. Implications from the findings have generated better insights for the business and economic histories of Macau
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; Thesis and Dissertations PhD in Business Administration (D-BA); University of Saint Joseph

Inquiry-Based Teaching and Learning as Cross-Cultural Educational Innovation - Pottier, Susan (University of Saint Joseph, 2011)
Inquiry-based Teaching and Learning is fundamental to modern western Science Education. This thesis argues that improving Science Education within a traditional Chinese educational setting can be realized by introducing Inquirybased Learning as a cross-cultural educational innovation - through the agency of a Science Learning Centre (SLC). The thesis evaluates the impact and uptake of the Inquiry-based approach, as seen through SLC activities that foster the professional development of Science teachers, and that build awareness of the approach at the community level. It also examines the process of establishing a SLC, and regional network, in Macau. The conceptual and substantive factors affecting the cross-cultural transfer of an Inquiry-based Teaching and Learning approach and the development of the SLC are explored through the theoretical lenses of Complexity Theory, Innovation and Change Theory; Social Networking Theory; and a range of Curriculum Development Theories. Central to the thesis is the analysis of three Episodes involving Inquiry-based training programmes facilitated by the SLC, and one Account of the development of the SLC itself: a series of Geoscience Inquiry-based learning workshops in Macau and Hong Kong; an invitational international professional development Training Programme provided in York by the National Science Learning Centre in England; an innovative Master’s in Education degree module which involved learning in an unfamiliar context; and finally, the creation of the Macau Science Learning Centre network as an agency for promoting Science Education in Macau. Furthermore, the thesis analyzes the multi-dimensional roles of the writer as participant, co-teacher, co-facilitator, researcher, ethnographer, theorist, and SLC manager. It incorporates aspects of educational innovation and change, teacher professional training, and the development of collaborative social networks. The research makes a unique contribution to the field of Science Education, especially in terms of the transfer and adaptability of an Inquiry-based approach into a traditionally Chinese educational setting through the agency of a SLC
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph